The impact of antioxidant-ciprofloxacin combinations on the evolution of antibiotic resistance in Pseudomonas aeruginosa biofilms - Doaa Higazy; Marwa N. Ahmed; Oana Ciofu (npj Biofilms and Microbiomes)
Abstract The evolution of antimicrobial resistance (AMR) in biofilms, driven by mechanisms like oxidative stress, is a major challenge. This study investigates whether antioxidants (AOs) such as N-acetyl-cysteine (NAC) and Edaravone (ED) can reduce AMR in Pseudomonas aeruginosa biofilms exposed to sub-inhibitory concentrations of ciprofloxacin (CIP). In vitro experimental evolution studies were conducted using flow cells and glass beads biofilm models. Results showed that combining CIP with antioxidants (CIP-AOs) effectively reduced the development of CIP resistance. Isolates from biofilms treated with CIP-AO had significantly lower minimum inhibitory concentrations (MICs) of CIP compared to those treated with CIP alone. Whole-genome sequencing (WGS) revealed mutations in the negative regulators of efflux pumps, nfxB, and nalC, in CIP-only treated biofilm populations. The occurrence of nfxB mutations was significantly lower in flow cell biofilms treated with CIP-AO compared to CIP alone. These findings suggest that antioxidants could play a role in mitigating AMR development in biofilms.